Silicon Photonics Devices Based On Microring Resonator For Optical Interconnect System - Abd Aziz, Nurul Nadia (2017)
Optical filter that utilizes silicon microring resonator (MRR) has been the promising element for future optical integrated circuits due to its various advantages such as small size,low insertion loss,high Q-factor and so on. This research begins with revision of some related research.The main objective is to model and develop silicon device configuration based on MRR that suitable for Wavelength Division Multiplexer (WDM) systems.The trade-off between those parameters such as ring radius, gap size and width of the core were investigated to study the effect to the MRR performance.The MRR was built by using the wave optic module by COMSOL Multiphysics 5.1. With this simulation,the terms that indicate the performance of MRR which are insertion loss (IL), extinction ratio (ER),free spectral range (FSR) were determined.The optimization work was done by using Taguchi Method where MRR had achieved 5.55% of ER and IL dropped 71.4%. Higher order microrings in the form of series-coupled MRR (SCMRR) and parallel-coupled MRR (PCMRR) were also modeled and investigated to determine the effect of the geometry and number of rings to the performance design.The comparison of single MRR,SCMRR and PCMRR were determined.Via simulation,the single MRR produced FSR of 42.0 nm with IL of 0.5 dB and ER of 25.0 dB.The 5th order of SCMRR produced FSR of 44.5 nm with ER of 11.5 dB and IL of 2.5 dB.Meanwhile,for the 5th order of PCMRR,the FSR was 42.6 nm with ER of 48.0 dB and IL of 0.5 dB.The performance of the developed filter device, PCMRR was tested on a WDM optical network using Optisystem software from Optiwave.It is found that PCMRR was successfully working on the WDM system where 1562 nm was successfully filtered out with 0.5 dB of IL.Besides that,to prove the potential of MRR as a unique element of passive and active devices,(de) multiplexer and sensor based MRR were also studied and presented in this project.The (de) multiplexer based MRR was achieved high FSR,low loss,crosstalk around 20 dB and suitable for working at C-band wavelength.In the meantime,the sensitivity of optical sensor based MRR was analyzed and calculated as 1x10-6 m/1℃.This result has achieved the sensor performance with low birefringence.